The way we build : restoring dignity to construction work - Erlich, Mark, 1949- (University of Illinois Press, 2023)
"The construction trades once provided unionized craftsmen a route to the middle class and a sense of pride and dignity often denied other blue-collar workers. Today, union members still earn wages and benefits that compare favorably to those of college graduates. But as union strength has declined over the last fifty years, a growing non-union sector offers lower compensation and more hazardous conditions, undermining the earlier tradition of upward mobility. Revitalization of the industry depends on unions shedding past racial and gender discriminatory practices, embracing organizing, diversity, and the new immigrant workforce, and preparing for technological changes. Mark Erlich blends long-view history with his personal experience inside the building trades to explain one of our economy's least understood sectors. Erlich's multifaceted account includes the dynamics of the industry, the backdrop of union policies, and powerful stories of everyday life inside the trades. He offers a much-needed overview of construction's past and present while exploring roads to the future"-- Provided by publisher.
Keywords: Construction industry -- United States.; Labor unions -- United States.; Building trades -- United States.; Construction -- Industrie -- États-Unis.; Métiers de la construction -- États-Unis.; Industries.; 20th Century.; United States.; HISTORY.; Labor & Industrial Relations.; POLITICAL SCIENCE.; Building trades; Construction industry; Labor unions; United States; Industry & industrial studies.; Industry.